AB0691 Six-Minute Walk Test in Systemic Sclerosis: A Systematic Review and Meta-Analysis. (9th June 2015) - Vandecasteele, E.; Decuman, S.; De Pauw, M.; Deschepper, E.; Brusselle, G.; De Keyser, F.; Smith, V.
Abstract : Background: Interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH) are nowadays the leading causes of death in patients with Systemic Sclerosis (SSc). Six-Minute Walk Test (6MWT) is a submaximal exercise test generally used for evaluating severity of disease, prognosis and response to treatment in patients with PAH and ILD. Data on 6MWT in SSc are scarce. Objectives: This study evaluates what is known about 6MWT in SSc by systematic review and meta-analysis. Methods: A systematic literature search on PubMed was performed using all combinations of keywords "SSc" and "6MWT". Two investigators evaluated the eligibility for the articles. Reference lists were searched for additional studies. Results: A total of 45 articles were included in the systematic review (36 of the 210 articles from literature search on PubMed and additional 9 articles from screening of the reference lists). Data of 38 of the 45 included articles were retained for the meta-analysis on Six-Minute Walk Distance (6MWD). The 6MWD of 1031 SSc-pulmonary hypertension (PH) patients was significantly lower than the 6MWD of 1401 SSc patients (283m [95% Confidence Interval [CI]: 255-311m] vs. 426m [95% CI: 401-451m] table 1 ). Within the SSc-PH group, consisting of a SSc-PAH, a SSc-ILD-PH and a SSc not specified PH subgroup, the estimated pooled mean 6MWD was clinically comparable between the SSc-PAH and SSc-ILD-PH subgroup with a strong overlap between the associated CIs. For 235 SSc-ILD patients, the pooled mean 6MWD was 381m (95% CI: 344-417m), which was clinically considerable lower as compared to the pooled mean of 1401 SSc patients, without reaching the level of statistical significance. Conclusions: This study is the first meta-analysis of the 6MWT in SSc, demonstrating that the 6MWD in SSc-PH patients (both SSc-PAH and SSc-ILD-PH) is significantly decreased compared to SSc patients. Disclosure of Interest: None declared